Troublesome science : the misuse of genetics and genomics in understanding race - DeSalle, Rob; Tattersall, Ian (Race, inequality, and health., 2018)
It is well established that all human beings today, wherever they live, belong to one single species. Yet even many people who claim to abhor racism take for granted that human "races" have a biological reality. From pharmacological researchers to the U.S. government, the dubious tradition of classifying people by race lives on. In Troublesome Science, Rob DeSalle and Ian Tattersall provide a lucid and compelling presentation of how the tools of modern biological science have been misused to sustain the belief in the biological basis of racial classification. Troublesome Science argues that taxonomy, the scientific classification of organisms, provides a cure for such misbegotten mischaracterizations. DeSalle and Tattersall explain how taxonomists do their job, in particular the genomic and morphological techniques they use to identify a species and to understand and organize the relationships among different species and the variants within them. They detail the use of genetic data to trace human origins and look at how scientists have attempted to recognize discrete populations within Homo sapiens. DeSalle and Tattersall demonstrate conclusively that these techniques, when applied correctly to the study of human variety, fail to find genuine differences, striking a blow against pseudoscientific chicanery. While the diversity that exists within our species is a real phenomenon, it nevertheless defeats any systematic attempt to recognize discrete units within it. The stark lines that humans insist on drawing between their own groups and others are nothing but a mixture of imagination and ideology.